Circulating VEGF and inflammatory bowel disease: a bidirectional mendelian randomization - Lin, Haishan; Cao, Bangwei (Frontiers in Genetics, 2024)
Prior observational studies have suggested an association between circulating vascular endothelial growth factor (VEGF) levels and inflammatory bowel disease (IBD). This study sought to demonstrate the directionality of the association between circulating VEGF and particular forms of IBD as well as if there is a causal relationship between them. We collected summary data from relevant genome-wide association studies (GWASs) to assess the validity of causality, and a two-sample bidirectional Mendelian randomization (MR) study and sensitivity testing were performed to assess the causal relationship between circulating VEGF and IBD risk, including Crohn's disease and ulcerative colitis. Our findings revealed a direct causal link between circulating VEGF and Crohn's disease (b 0.195, se 0.078, p < 0.013). However, neither circulating VEGF nor ulcerative colitis were shown to be causally linked (p > 0.025), nor was there proof of a reverse causal relationship from IBD to VEGF. In conclusion, circulating VEGF shows a cause-and-effect relationship with Crohn's disease.